Late Carboniferous N-MORB-type basalts in central Inner Mongolia, China: Products of hydrous melting in an intraplate setting? - Pang, C.; Wang, Xuan-Ce; Xu, B.; Zhao, J.; Feng, Y.; Wang, Y.; Luo, Z.; Liao, W. (Elsevier BV, 2015)
Petrogenesis of the ca. 310 Ma Benbatu basalts in central Inner Mongolia is crucial for constraining the evolution of the Xing'an Mongolia Orogenic Belt (XMOB), eastern segment of the Central Asian Orogenic Belt. The Benbatu basalts have low initial 87Sr/86Sr ratios (0.7042–0.7048), positive εNd(t) (+ 8.99 to + 9.24) and εHf(t) values (+ 15.38 to + 15.65), and are characterized by relatively flat rare earth element patterns and enrichment of Rb, U, Pb, Zr and Hf, but depletion of Nb, Ta, Sr and Ti, resembling those of the normal Mid-Ocean-Ridge Basalt (N-MORB). Variations of trace element ratios (e.g., Sm/Yb and La/Sm) suggest that the basalts were derived from spinel peridotites, with a melting depth of < 60–85 km. The characteristics of enrichment of Zr and Hf and depletion of Sr distinguish the Benbatu basalts from typical arc basalts and back arc basin basalts. The arc-like geochemical signatures (i.e., enrichment of large ion lithophile elements and depletion of Nb and Ta) are attributed to hydrated mantle source that may be caused by fluids released from stagnant oceanic slabs in the mantle transition zone. Integrating geological evidences with geochemical and isotopic features of the Benbatu basalts, we proposed that these basalts were produced under an intraplate extensional setting during the Late Carboniferous. The genesis of the Benbatu basalts therefore argues for the pre-Carboniferous accretion of the XMOB and highlights the importance of the deep-Earth recycling water in the generation of the Late Carboniferous magmatism in this region.